In vitro comparison of the effect of fondaparinux and enoxaparin on whole blood tissue factor-triggered thromboelastography profile - Gerotziafas, Grigoris T.; Chakroun, Tahar; Samama, Meyer M.; Elalamy, Ismail (Thrombosis and Haemostasis, 2004)
Fondaparinux and enoxaparin are both effective and safe in preventing post-operative venous thromboembolism. However, neither of them significantly influence the conventional clotting tests. We compared the influence of clinically relevant concentrations of fondaparinux and enoxaparin on normal whole blood (WB) thromboelastographic profiles after triggering TF-pathway with minimal amount of thromboplastin. Diluted thromboplastin was added to WB samples supplemented with buffer (control), fondaparinux (0.25; 0.5; 1µg/ml), or enoxaparin (0.1; 0.5; 1anti-Xa lU/ml). Four parameters were analyzed, R: clotting time, K: time required to reach an amplitude of 20 mm, αangle: measurement reflecting clot development kinetics and MA: maximal amplitude. At concentrations used in prophylaxis, both enoxaparin (0.1 anti-Xa lU/ml) and fondaparinux (0.25 µg/ml which correspond to 0.27 anti-Xa lU/ml) significantly prolonged the R and K times, but did not significantly modify the a angle as compared to the control. At concentrations observed after administration of curative doses for the treatment of DVT (≥0.5 anti-Xa lU/ml for enoxaparin and ≥0.5 ug/ml for fondaparinux) both drugs induced a significant increase of R and K times, and a significant decrease of the αangle (p <0.05). In contrast to fondaparinux, enoxaparin at concentrations equal to or higher than 0.5 anti-Xa lU/ml significantly reduced MA. The present study provides evidence that the whole blood TF-triggered TEG assay is sensitive to the presence of clinically relevant concentrations of enoxaparin or fondaparinux. Moreover, the angle may be used in order to distinguish the effect of prophylactic and therapeutic concentrations, since it was significantly reduced by the later ones. Further studies are needed to evaluate the clinical usefulness of whole blood TF-triggered TEG assay for the monitoring of treatment with enoxaparin or fondaparinux.
Keywords: Thromboelastography; fondaparinux; enoxaparin; tissue factor; thrombin generation